Heterosis and Diallel Analysis for Grain Yield, Yield Attributes and Physiological Traits in Barley (Hordeum vulgare L.) - Patel, Supriya; Kumar, Vishnu; Saini, Manoj Kumar; Singh, Anshuman; Singh, Sultan; Singh, K. K.; Naveen, Aavula; Krishna, Vemula Anjula; Chaturvedi, S. K. (International Journal of Bio-resource and Stress Management, 2024)
The present study was carried out during November–April, 2019–2020 and 2020–21 with eight diverse barley genotypes and their developed 28F1s (half diallel, excluding reciprocals) to ascertain gene effects, hetrosis and correlations for grain yield, yield attributes and physiological traits under water limited conditions of Bundelkhand region. Days to heading and days to maturity exhibited general mean values of 86 days and 127 days, respectively. The parental genotypes, DWRB180, RD2794 and RD2899 showed early spike emergence and maturity. The cross combinations, namely DWRB160 /DWRB180, DWRB180/RD2907 and BH946/RD2552 were promising for flag leaf length and width. The GCA effects were significant and prevalent for all the characters, except days to heading, plant height and tillers count. The parents, DWRB160 (5.29**) and BH902 (1.59**) depicted high GCA effects for 1000 grain weight. The parents, DWRB180, RD2552, and BH946 exhibited significant positive GCA effects for leaf area index and chlorophyll fluorescence, whereas the genotypes, RD2907, BH946 and RD2899 showed higher GCA effects for chlorophyll content. Grain yield exhibited significant positive correlations with flag leaf width (0.60**), tillers per meter (0.35*), grains per spike (0.39*), harvest index (0.53**), chlorophyll content (0.69**), leaf area index (0.49**) and chlorophyll fluorescence (0.68**). The parents, BH946, DWRB180 and RD2907 and the hybrids, RD2552/DWRB180, BH902/RD2794, DWRB160/DWRB180 and BH946/RD2907 were found promising for yield and yield attributes in the dry agro-ecology of Bundelkhand region. The crosses, DWRB160/BH902 and DWRB160/BH946 can be explored for developing superior segregants for malt barley breeding.